Influence of Cardiovascular Risk Factors Among Patients with Covid 19 Infection and its Association with In-Hospital Outcome – A Multicentre Prospective Observational Study - Rahman, Mohammad Arifur; Ahmed, Mohsin; Anwar, Kazi Md Rubayat; FarJana, Jinat; Hasan, Md Kamrul; Mahmod, Md Salim; Hossain, Md Delwar; Huda, Reaz Mahmud; Morshed, Md Golam; Sikder, Anjan Kumar; et al. (Bangladesh Heart Journal, 2024)
Introduction: The global spread of COVID-19, first identified in Wuhan, China, in December 2019, has ignited an unprecedented ongoing global pandemic. Risk stratification of these patients is crucial to optimize the use of hospital resources. Several associations with adverse outcomes in COVID-19 patients have been identified, including factors that also predispose to cardiovascular disease (CVD), such as older age, male sex, hypertension, overweight and diabetes. In this context we designed this study to observe Association of Cardiovascular risk factors with patients infected with Covid 19 and it’s in-hospital outcome. Materials and Methods: In this prospective observational study total 408 adult patients who were reverse transcription polymerase chain reaction (Rt-PCR) positive for COVID-19 were included. They were admitted in Sarkari Karmachari Hospital, Kuwait Bangladesh Friendship Government Hospital and Dr. Sirajul Islam Medical College between June 2020 to June 2022. Patients with severe comorbidities like Acute myocardial infarction, Stroke, Acute kidney injury, malignancy and pregnant women were excluded from the study. Appropriate informed written consent was obtained. Demographic and clinical data were correlated with outcome. The statistical analysis was carried out using the Statistical Package for Social Sciences version 22.0 for Windows (SPSS Inc., Chicago, Illinois, USA). Qualitative variables were expressed as frequency and percentage. Quantitative variables were expressed as mean ± standard deviation and median. Test of significance was performed by unpaired t-test for quantitative variable and Chi square test for qualitative variables. In addition, multivariate logistic regression analysis of possible risk factors was done to determine the association with outcome by calculating odds ratio with 95% confidence intervals. A p value <0.05 was be considered as significant. Results: The mean age of participants was 45.2±13.4 years among them 263 (64.5%) were male and 145 (35.5%)were female. According to BMI maximum male 126 (47.9%) were normal weight group whereas maximum female 63(43.4%) were obese. Considering cardiovascular risk factors among male and female Smoking were 160 (60.8%) vs. 38 (26.2%), Hypertension were 105 (39.9%) vs. 65 (44.8%), Diabetes Mellitus were 71 (27.0%) vs 55 (37.9%), Dyslipidemia were 69 (26.2%) vs. 36 (24.8%), Family history of CVD were 55 (20.9%) vs.20 (13.8%) and Clustering of risk factors (≥2 factors) were 117 (44.5%) vs. 74 (51.0%). Among the study population 81 (19.9%) needed oxygen therapy , 50 (12.3%) needed Non-invasive ventilation, 34 (8.3%) patients needed Mechanical Ventilation, Among the study subjects total 27 (6.61%) expired and maximum number of patients 15 (55.6%) were in 61-80 years age group. Regression analysis for the predictors of adverse in hospital outcome among the Cardiovascular risk factors showed Age (>60yrs) (p= 0.034), BMI (>25) (p= 0.026), Smoking (p= 0.041), Hypertension (p= 0.037) Diabetes Mellitus (p= 0.013), Dyslipidemia (p= 0.021) and Clustering of risk factors (≥2) (p= 0.012) were statistically significant contributors. Conclusion: In conclusion, this study shows that Age (>60yrs), BMI (>25), Smoking, Hypertension, Diabetes Mellitus, Dyslipidemia, clustering of risk factors (≥2) have greater risk of adverse outcomes including death from COVID-19. It is recommended that individuals with cardiovascular risk factors, especially older men and women, should be focus of public health measures and must be informed regarding increased risk of death in COVID-19. It is likely that with proper preventive and therapeutic interventions the higher risk of adverse outcomes in COVIDF-19 patients with cardiovascular risk factors can be mitigated. We need to be more vigilant in controlling CVD risk factors since it not only increases the morbidity of non-communicable diseases, but also poses to and worsens the outcome of communicable diseases. Bangladesh Heart Journal 2024; 39(2): 85–92